Post-emergent applications of isolated and combined herbicides on corn culture with cp4-epsps and pat genes - Krenchinski, Fabio Henrique [UNESP]; Albrecht, Alfredo Júnior Paiola; Salomão Cesco, Victor José [UNESP]; Rodrigues, Danilo Morilha [UNESP]; Pereira, Vinicius Gabriel Caneppele [UNESP]; Albrecht, Leandro Paiola; Carbonari, Caio Antonio [UNESP]; Victória Filho, Ricardo (Elsevier, 2018)
For optimum yield, it is necessary to incorporate a good weed control into the system. This study aimed to determine the effects of a post-emergent application of different herbicides (individually and combined) on corn presenting cp4-epsps and pat genes. Field studies were conducted on the corn hybrid 2B810 with the cp4-epsps and pat genes in the agricultural years 2012/13 and 2013/14 and included 8 treatments with isolated and combined application of glyphosate, glufosinate-ammonium, and atrazine. The variables evaluated were chlorophyll type a and b, total chlorophyll index, stem diameter, height of the cob insertion, prolificacy index, first height, second height, yield, and volume of 100 grains. The combination of all three herbicides hindered the yield of corn cultures. This practice therefore requires caution when applied to weed management. The combination of two herbicides did not affect the final height or yield and may be a useful method of weed management in future.
Keywords: Association herbicides; Liberty link; Roundup ready